Analysis of the activities of domestic TV channels in the media market - Aldabergenova, Zh.Zh.; Mamankul, А.А.; Pernebekova, А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article analyzes the activities, directions, projects in their broadcast schedule, and their place in the rating table of television channels registered in the Ministry of Information and Social Development of the Republic of Kazakhstan and operating in the domestic media market. Kantar («TNS Central Asia» LLP) has been monitoring and studying the rating of republican TV channels in the media market for 20 years. Based on the research provided by the company, domestic TV stations create a media plan and broadcast schedules. This is the only company monitoring the media market in Kazakhstan. Considering that the study of only one company is a biased opinion, the authors conducted a special survey among TV viewers. The Kantar company and the survey data were compared and the TV viewer demand was analyzed. The analysis also takes into account the place of residence, age, gender of the viewer. Based on the results of these studies, an analysis of the activities, content, and social media accounts of several Republican TV channels was carried out